Effect of simulated in vitro upper gut digestion of processed cowpea beans on phenolic composition, antioxidant properties and cellular protection. (December 2021) - Apea-Bah, Franklin B.; Serem, June C.; Bester, Megan J.; Duodu, Kwaku G.; Beta, Trust
Graphical abstract: Highlights: In vitro digestion causes phenolic-peptide complex formation in processed cowpeas. In vitro digestion increases radical scavenging activity of processed cowpea beans. Digests from processed cowpeas inhibit endotoxin-induced cellular NO production. Digests from processed cowpeas protect DNA and fibroblasts from oxidative damage. Abstract: The effect of simulated in vitro upper gut digestion on the phenolic composition and antioxidant properties of processed cowpea beans was studied. The samples comprised four cowpea cultivars: a cream, brownish-cream and two reddish-brown cultivars. Dry cowpea seeds were soaked in water, blended into paste and deep-fried in vegetable oil. The fried samples were taken through in vitro upper gut digestion followed by freeze-drying of the supernatant. Phenolic composition of extracts from the supernatants were determined using HPLC-MS. Radical scavenging activities were documented using the TEAC, ORAC and nitric oxide (NO) assays. In vitro digestion of the processed cowpeas resulted in phenolic-peptide complexes that were identified for the first time, and decreased extractable phenolic compounds. However, the radical scavenging activities increased. The processed cowpeas and their digests inhibited cellular NO production, and oxidative DNA and cellular damage. In conclusion, deep-fried cowpeas when consumed, could potentially help alleviate oxidative stress-related conditions.